Economic Diversification in Bahrain - Abu Wadi, Rami Mohammad; Bashayreh, Ala’ G. (International Journal of Economics and Financial Issues, 2018)
The study aims at analyzing the effect of economic diversification on economic growth in Bahrain for the period (1980-2014). For this purpose, many indicators were developed using The Herfindahl-Hirschman index (HHI) and five variables: real GDP, exports, imports, government revenues and fixed capital formation. Results reveal a weak diversification in the Bahraini’s economy besides a positive effect of diversification on the economic growth in Bahrain. In fact, no significant relationship between Herfindahl index and the growth of real GDP. Keywords: Economic Diversification, Economic Growth, Herfindahl-Hirschman index. JEL Classifications: L25, O47